2017
DOI: 10.1039/c7cp00722a
|View full text |Cite
|
Sign up to set email alerts
|

Thiocyanates as attractive redox-active electrolytes for high-energy and environmentally-friendly electrochemical capacitors

Abstract: This manuscript reports on the novel insight into the development of high voltage carbon/carbon electrochemical capacitors operating in aqueous solutions of alkali metals and ammonium thiocyanates (KSCN, NaSCN, LiSCN, and NHSCN). The effect of salt concentration, electrode porosity and current collectors on the capacitance value, system stability, and power performance has been investigated. Therefore, thiocyanate-based electrolytes were recognized as cheap and highly conductive electrolytic solutions (up to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Using neutral electrolyte essentially, electric double-layer response is observed within the electrochemical stability window of water. When the cell contains 7 mol L −1 KSCN, a significant redox contribution at high voltages is found together with EDL response, already thoroughly described [12]. The electrode potential profiles within the time of the experiment seem to be almost linear for Li 2 SO 4 .…”
Section: Resultsmentioning
confidence: 68%
“…Using neutral electrolyte essentially, electric double-layer response is observed within the electrochemical stability window of water. When the cell contains 7 mol L −1 KSCN, a significant redox contribution at high voltages is found together with EDL response, already thoroughly described [12]. The electrode potential profiles within the time of the experiment seem to be almost linear for Li 2 SO 4 .…”
Section: Resultsmentioning
confidence: 68%
“…The most popular ones in the aqueous medium are halides (bromide and iodide anions) (Frackowiak et al, 2012;Chen et al, 2015;Menzel et al, 2015;Sathyamoorthi et al, 2016). However, recently, a different group has also been implemented as a redox-active electrolytepseudohalides (thiocyanates and selenocyanates) (Gorska et al, 2017;Bujewska et al, 2019).…”
Section: Energy Storage Devicesmentioning
confidence: 99%
“…[32] Ideal redox-active couples as electrolyte additives are supposed to have the followingc haracteristics:1 )forming stable solutionsw ithout reactingw ith water or co-electrolyte (consists of neutrals alt or another redox-active couple);2 )excellent water solubility;3 )strong connection with electrode surface through either electrostatic or physicalm ethods. As eries of redox couples were investigated, such like Br À /Br 3 À , [33] I À / I 3 À , [34] [Fe(CN) 6 ] 4À /[Fe(CN) 6 ] 3À , [35] SCN À /CNO À , [36] benzylv iologen (BV 2 + /BV + ), [32] methyl viologen (MV 2 + /MV + ), [32] ethyl viologen (EV 2 + /EV + ), [32] heptyl viologen (HV 2 + /HV + ), [32] methylene blue (MB + /MB), [37] leucoindigo carmine/indigo carmine/dehydroindigo carmine (LC/IC/DC), [38] quinones (HQ/Q), [39] andv anadium complexes (VO 2 + /VO 2 + ). [40] For instance, Hwang et al [35] demonstrated ar emarkable % 5-fold increment in the capacitance of CSCs by adding 0.1 m [Fe(CN) 6 ] 4À /[Fe(CN) 6 ] 3À into 1 m Na 2 SO 4 electrolyte.…”
Section: Aqueouselectrolytesmentioning
confidence: 99%
“…Reduction potentials of the couples considered relativetot he thermodynamic stability window of water at neutral pH (white region). The lines coloredinr ed, green and blue are for couples stable in acidic (1 m acid), neutral,and basic(1m base) conditions, respectively.Reproduced with permissionfrom Ref [36]. Copyright 2015, Nature Publishing Group.…”
mentioning
confidence: 99%